Quantitative genetics of polar bear (Ursus maritimus) behaviours - Kathan, Leah (2024)
Conflict plays a central role in sexual selection by shaping the behaviours and traits that contribute to reproductive success. It drives competition between individuals, influences mate choice and mating strategies, and ultimately shapes the evolution of sexual dimorphism, courtship displays, and other aspects of reproductive behaviour in many species. Informing conservation management strategies aiming at reducing human-wildlife conflicts involves understanding the interplay of genetic, social, and environmental effects on behavioural phenotypic variation. The objectives of this thesis were to investigate the heritable and non-heritable dynamics shaping complex human-polar bear (Ursus maritimus) conflict risk behaviour observed in Churchill, Manitoba. The study aims to understand the influence of climate change and human settlements on population-level behaviour, and understand the individual-level influences of innate, social, and remaining environmental cues driving polar bear conflict risk behaviour expressed by individuals within the Western Hudson Bay subpopulation. These concepts build on the foundations of quantitative genetics and animal behaviour, using data from an extensively monitored wild polar bear subpopulation near Churchill, Manitoba. The findings suggest that conflict risk behaviour is very closely tied to individuals’ ability to survive and reproduce, and that polar bears have a high affinity for environmental learning and for avoiding serious conflicts. Dynamics in conflict risk behaviour over time underscore the influence of environmental stressors, contrasting with minimal cohort effects. Conservation management strategies focused on reducing human-wildlife conflicts should aim to improve the environmental conditions for wildlife by preserving habitat quality and connectivity. October 2024 University of Manitoba Graduate Fellowship